2019
DOI: 10.1002/ceat.201900172
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sodium Dodecyl Sulfate on the Continuous Crystallization in Microfluidic Devices Using Microbubbles

Abstract: Introducing microbubbles in a microreactor for continuous crystallization increases the nucleation rate and also prevents clogging. Adding surfactants affects the microbubble generation as it reduces their size, increases their frequency of formation and consequently also the interfacial area per unit volume of reactor acting as heterogeneous surface for nucleation. Here, the effect of sodium dodecyl sulfate (SDS) on both the microbubble generation and the continuous crystallization of paracetamol is investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…(iv) The droplet technique can be combined with the double-pulse technique. Disadvantages: (i) Surfactants are extensively used in the generation of droplets to stabilize and prevent coalescence 117 , but might affect nucleation 101,[118][119][120] . If no surfactants are used, heterogeneous nucleation might occur on the gas-liquid interface 121 .…”
Section: Advantages: (I) the Droplet Technique Adheres Well To The Mnm Technique Because Of The Extremely Small Volumes Of The Droplets (mentioning
confidence: 99%
See 1 more Smart Citation
“…(iv) The droplet technique can be combined with the double-pulse technique. Disadvantages: (i) Surfactants are extensively used in the generation of droplets to stabilize and prevent coalescence 117 , but might affect nucleation 101,[118][119][120] . If no surfactants are used, heterogeneous nucleation might occur on the gas-liquid interface 121 .…”
Section: Advantages: (I) the Droplet Technique Adheres Well To The Mnm Technique Because Of The Extremely Small Volumes Of The Droplets (mentioning
confidence: 99%
“…( i ) Surfactants are extensively used in the generation of droplets to stabilize and prevent coalescence, but this might affect nucleation. , If no surfactants are used, heterogeneous nucleation might occur on the gas–liquid interface . ( ii ) Equations from the MNM are used.…”
Section: Part Ii: Microfluidic and Microvial Crystallizersmentioning
confidence: 99%
“…The variety of morphologies obtained showed that the type of excipient had an influence on the habit formation of the ITZ in suspension The morphologies of the ITZ particles generated with six different stabilizers were Figure 5C rod-shaped with rough edges, Figure 5D elongated-rod-shaped with a rough surface, Figure 5E thin-rod-shaped but agglomerated, Figure 5F thin rods stacked upon each other in a hay-like formation, Figure 5G needle-like in shape, and Figure 5H uniformly sized elongated tabular structures for POL 188, POL 338, POL 407, PVP K30, NaCMC, and Vit E TPGS 1000, respectively. The variety of morphologies obtained showed that the type of excipient had an influence on the habit formation of the ITZ in suspension [59,60]. Therefore, it is critical to understand how excipients influence ITZ crystallization, which can provide experimental support for rational excipient selection for suspension optimization [61] during the SCT-CLASC process.…”
Section: Stabilizer Selectionmentioning
confidence: 99%
“…14 The droplets must therefore be kept isolated to prevent merging, the evaporation of water can occur and result in supersaturation changes, and the addition of surfactants to stabilize droplets can influence nucleation. 13,15 In order to avoid the interference from surfactants, different means have been developed to prevent droplet merging in a surfactant-free system. A long tubing is employed to avoid coalescence for protein crystallization with a long incubation time.…”
Section: Introductionmentioning
confidence: 99%
“…Device fouling can readily occur when reaction solutions are combined to form droplets, and measurements are often conducted over long times . The droplets must therefore be kept isolated to prevent merging, the evaporation of water can occur and result in supersaturation changes, and the addition of surfactants to stabilize droplets can influence nucleation. , In order to avoid the interference from surfactants, different means have been developed to prevent droplet merging in a surfactant-free system. A long tubing is employed to avoid coalescence for protein crystallization with a long incubation time. , However, the throughput is not satisfied; a length of 2 m has to be used to store 200 droplets.…”
Section: Introductionmentioning
confidence: 99%